From the closet to the altar courts, backlash, and the struggle for same-sex marriage - Klarman, Michael J (New York Oxford University Press, 2013)
"Same-sex marriage, a politically and culturally untenable idea only a quarter century ago, has become one of the most controversial issues in American life. Social conservatives are adamantly opposed to it and vote-conscious liberal politicians tiptoe around it, but an emerging majority's support for it makes it seem all but inevitable. While most observers seem to think that the legalization of gay marriage across the nation will occur at some point in the near future, in the meantime it continues to generate a sharp political backlash that has helped its opponents score political victories (even if they prove to be short-lived). If most young people support gay marriage, and if there are clear indicators that a majority of the population will support it in the very near future, why is the backlash so strong? As Michael Klarman will show in From the Closet to the Altar, it is because its proponents have adopted a court-centered approach for advancing their cause. In many states, advocates have taken to the courts and argued that bans on gay marriage are denials of civil rights. They have followed the path of earlier civil rights advocates, who also chose the court rather than the political arena as a forum to decide issues. But as Klarman shows, this tactic comes with clear costs. Using the courts to leapfrog public opinion can actually set a cause back because court decisions generate backlashes. Usually, judges are neither elected nor beholden to public opinion, and they are easily pegged as unaccountable elites by opponents. Klarman, who has examined virtually every state-level judicial decision and all of the legislative attempts to overturn same-sex marriage, contends that the movement has in many respects not only hurt its own cause by generating populist backlash, but has created a countervailing social movement that works against progressive causes on a host of other issues. Given the irreversible tectonic shift in public opinion regarding the issue, he argues that it will occur anyway. By providing such fuel to its opponents (much like with Roe v. Wade), the movement is in danger of creating a powerful countermovement that will use the issue for proponents of gay rights for years to come. Concise yet sweeping in scope, From the Closet to the Altar is not only a worthy successor to his Bancroft Prize-winning From Jim Crow to Civil Rights, it will reshape how we think about the issue"--
"Bancroft Prize-winning historian and legal expert Michael Klarman here offers an illuminating and engaging account of modern litigation over same-sex marriage. After looking at the treatment of gays in the decades after World War II and the birth of the modern gay rights movement with the Stonewall Rebellion in 1969, Klarman describes the key legal cases involving gay marriage and the dramatic political backlashes they ignited. He examines the Hawaii Supreme Court's ruling in 1993, which sparked a vast political backlash--with more than 35 states and Congress enacting defense-of-marriage acts--and the Massachusetts decision in Goodridge in 2003, which inspired more than 25 states to adopt constitutional bans on same-sex marriage. Klarman traces this same pattern--court victory followed by dramatic backlash--through cases in Vermont, California, and Iowa, taking the story right up to the present. He also describes some of the collateral political damage caused by court decisions in favor of gay marriage--Iowa judges losing their jobs, Senator Majority Leader Tom Daschle losing his seat, and the possibly dispositive impact of gay marriage on the 2004 presidential election. But Klarman also notes several ways in which litigation has accelerated the coming of same-sex marriage: forcing people to discuss the issue, raising the hopes and expectations of gay activists, and making other reforms like civil unions seem more moderate by comparison. In the end, Klarman discusses how gay marriage is likely to evolve in the future, predicts how the U.S. Supreme Court might ultimately resolve the issue, and assesses the costs and benefits of activists' pursuing social reforms such as gay marriage through the courts"--
Includes bibliographical references (p. 260-265) and index.
Keywords: Same-sex marriage -- Law and legislation -- United States -- History; Gay couples -- Legal status, laws, etc. -- United States -- History; Same-sex marriage -- Law and legislation -- United States -- States; Civil unions -- Law and legislation -- United States; Law / Civil Rights; Political Science / Public Policy / Social Policy